Influence of the Cutting Edge Contact Area Size CBN Insert on Surface Roughness In Turning of AISI1050 Steel - Sriswat, Manus; Thavornwat, Chalermsak; Chanchana, Atthakorn (Journal of Advanced Development in Engineering and Science, 2023)
The general cylindrical turning process can control the surface quality with roughness varied between 3.2 and 0.4 micrometers. However, to control the surface quality with roughness below 0.4 micrometer, the special turning process with the special cutting material and the additional polishing process are required, especially lathing of steels with slight hardness, i.e. low- and medium-carbon steels. This research aimed to reduce the procedures and time of the turning process for a piece of work that requires high surface quality. This research also created the turning process of low- and medium-carbon steels obtaining the surface roughness below 0.4 micrometers by only one turning process. The various sizes of cutting edge contact area of CBN insert affecting the surface quality of lathed AISI 1050 steels were investigated. In this experiment, the sizes of cutting edge contact area of CBN insert were varied to be 5, 10, 15, 20 and 25 micrometers when the standard cutting edge contact area of CBN insert is 0 micrometers under specific conditions of experimental turning, i.e. cutting speed at 280 meters per minute, feeding rate at 0.05 millimeter per round, feeding depth at 0.1 millimeter without coolants. One-Way ANOVA technique was employed to test hypotheses with statistical significance at 0.05. The findings reveal that CBN inserts that had contact areas of cutting edge contact area at 0 – 20 micrometers could be used to control the diameter with tolerance ± 0.005 millimeters. Meanwhile, CBN inserts that were adjusted cutting edge contact area to have contact areas at 15 micrometers could turn AISI 1050 steel with surface roughness at 0.286 micrometers; that is, the surface quality was at the same level of surface of the cut and polished works.